Resources Allocation Optimization for Real Time Traffic in LTE Cellular Network - Mukasine, Angelique; Ahishakiye, Faustin; Musabe, Richard; Bajpai, Gaurav (International Journal of Research in Electronics and Computer Engineering, 2016)
Nowadays, a threefold real time traffic system is developing where voice, video and data traffic coexist in cellular networks. Since there are a limited number of resources, some of the traffic cannot be served in the real time. For example when all channels are occupied the remaining user equipments (UEs) requesting the service are blocked. Therefore a resource allocation optimization for real time traffic needs to be studied in this context. Significant studies have been conducted with a common objective of maximizing data rate and adaptive channel borrowing, however they don’t mitigate the problem of network coverage at the cell edge and spectrum is not shared efficiently among data and voice traffic. In this paper we propose three resource allocation methods for voice/data integrated in cellular network. In the First case, both voice and data traffic are assigned separate resources and the communication is in a dedicated mode. In the second case, we assign different resources but we allow the reuse of one of the traffic resources either voice or data provided that the interference is well managed. Thirdly we propose the method of borrowing the idle resources depending to the UE transmitting power of new call arrival. Our resource allocation schemes were developed based on blocking probability and weighted cell utilization mathematic model. MATLAB simulation results show that the performance of our proposed schemes in terms of UE blocking probability and cell weighted utility is better compared to cellular alone.
Keywords: Resource Optimization; LTE; Real-Time Traffic; Cell utility